2018
DOI: 10.2215/cjn.09920917
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Racial Disparities in Kidney Transplantation among Health Care Providers in Dialysis Facilities

Abstract: Among a limited sample of dialysis facilities with low waitlisting, provider awareness of racial disparities in kidney transplant waitlisting was low, particularly among staff who may have more routine contact with patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…This is especially true given that we found that patients most often turned to their physicians for information when choosing centers, but prior studies have shown that healthcare providers have limited awareness of the allocation system or of disparities in kidney transplantation. 24,25 Disparities in patient education about transplant have direct effects on access to transplantation, and prior studies have found that patient education has the ability to reduce racial and socioeconomic disparities in completion of transplant evaluation. 11,26 Furthermore, prior studies have found that patients with lower education attainment were more likely to report psychosocial concerns regarding pursuing transplantation, and less likely to believe transplantation would be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially true given that we found that patients most often turned to their physicians for information when choosing centers, but prior studies have shown that healthcare providers have limited awareness of the allocation system or of disparities in kidney transplantation. 24,25 Disparities in patient education about transplant have direct effects on access to transplantation, and prior studies have found that patient education has the ability to reduce racial and socioeconomic disparities in completion of transplant evaluation. 11,26 Furthermore, prior studies have found that patients with lower education attainment were more likely to report psychosocial concerns regarding pursuing transplantation, and less likely to believe transplantation would be advantageous.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, vulnerable patients or those with lower education or health literacy levels may have limited awareness of the survival benefit of transplantation compared to other modalities . Coupled with evidence of limited provider awareness of several aspects of the transplant system, including evidence of disparities in access, research suggests that incorporating patient preferences as early as possible into the process could promote shared decision‐making.…”
Section: Discussionmentioning
confidence: 99%
“…There is a large body of literature trying to explain these differences. No definite explanations have been described, and the majority of researchers agree that it is the result of a combination of environmental (eg, a western diet, sedentary life style, and increased consumption of salt), genetic (predisposition to salt retention and APOL 1 genotype), and possibly social (access to care for early diagnosis of hypertension and affordability of treatment) factors …”
Section: Introductionmentioning
confidence: 99%
“…It increases patients’ life expectancy, improves quality of life, and is more cost‐effective than dialysis. Certain studies have reported differences in access to kidney transplantation between African Americans and Whites . Although African Americans comprise close to 37% of the kidney waiting list, they receive 25% of deceased and 14% of living donor transplants .…”
Section: Introductionmentioning
confidence: 99%